2014
DOI: 10.1080/1059924x.2014.884397
|View full text |Cite
|
Sign up to set email alerts
|

Improving Eye Safety in Citrus Harvest Crews Through the Acceptance of Personal Protective Equipment, Community-Based Participatory Research, Social Marketing, and Community Health Workers

Abstract: For the last 10 years, the Partnership for Citrus Workers Health (PCWH) has been an evidence-based intervention program that promotes the adoption of protective eye safety equipment among Spanish-speaking farmworkers of Florida. At the root of this program is the systematic use of community-based preventive marketing (CBPM) and the training of community health workers (CHWs) among citrus harvester using popular education. CBPM is a model that combines the organizational system of community-based participatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…It should be noticed that only few studies presenting specific training methods 41,47,52,53 reported some comparisons between experimental (i.e. trained with the new materials) and control groups; in addition, only one study 43 Secondly, the majority of reviewed training programs targeted SB while migrant farmworkers' SAB are less frequently considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noticed that only few studies presenting specific training methods 41,47,52,53 reported some comparisons between experimental (i.e. trained with the new materials) and control groups; in addition, only one study 43 Secondly, the majority of reviewed training programs targeted SB while migrant farmworkers' SAB are less frequently considered.…”
Section: Discussionmentioning
confidence: 99%
“…lay health educators, community health workers, health promoters). Five pilot studies 39,[46][47][48]52 assessed the efficacy of a model combining community-based participatory research with peer to peer education. At the end of these programs, an increased use of PPE compared to baseline or control groups was observed in all studies.…”
Section: Effectiveness Of Specific Training Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was conducted in partnership with various stakeholders (e.g., the Professional Dairy Producers of WI, the Mexican Consulate of St. Paul) who have extant knowledge of and experience with immigrant, Latino/a dairy workers. See Tovar-Aguilar et al (101) for an example of another program that utilized many of the best practices outlined in this review to promote eye safety among Latino/a citrus harvest workers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 17 ] We believe that its use will protect workers from work-related injuries and consequent morbidity. Studies evaluating safety eyewear usage in agriculture come mostly from the West,[ 26 27 28 29 30 31 32 ] but because of the different farming practices and sociocultural characteristics, their results cannot be directly extrapolated to the Indian scenario. We are not aware of any study evaluating the use of safety eyewear among Indian agricultural workers.…”
mentioning
confidence: 99%